2018
DOI: 10.1515/revneuro-2017-0037
|View full text |Cite
|
Sign up to set email alerts
|

Population-based differences in immune system response contribute to an increased risk of schizophrenia in African migrants?

Abstract: Among the highest incidences of schizophrenia is the one documented in second-generation migrants of African descent in the Western countries. Interestingly, people of African and European ancestry demonstrate significant genetic-based differences in immune system regulation and response. As a result, the pro-inflammatory phenotype is more pronounced in people of African descent than it is in Europeans. At the same time, the role of the immune system in the etiology of schizophrenia is gaining increased recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…At the same time, schizophrenia rates are up to nine times higher in African migrants to Western countries compared to non‐migrants of European decent . It would be interesting to investigate if there is a potential trade‐off between a more pronounced pro‐inflammatory phenotype during neurodevelopment (required for successful combat against certain microbial agents) and increased risk for schizophrenia, which is characterized by an overactive immune response . Apart from immune‐system genes, genes involved in adaptations to different climates and/or nutrients could also be of interest to schizophrenia etiology.…”
Section: Evolutionary Theories Linking Schizophrenia To Adaptive Traitsmentioning
confidence: 99%
“…At the same time, schizophrenia rates are up to nine times higher in African migrants to Western countries compared to non‐migrants of European decent . It would be interesting to investigate if there is a potential trade‐off between a more pronounced pro‐inflammatory phenotype during neurodevelopment (required for successful combat against certain microbial agents) and increased risk for schizophrenia, which is characterized by an overactive immune response . Apart from immune‐system genes, genes involved in adaptations to different climates and/or nutrients could also be of interest to schizophrenia etiology.…”
Section: Evolutionary Theories Linking Schizophrenia To Adaptive Traitsmentioning
confidence: 99%
“…Laureat je Svante Pabo (Svante Paabo), lekar i naučnik, koji je prvi sekvencirao genom Neandertalca [4] . Time je omogućio ekspanziju komparativnih studija (studija koje porede karakteristike dve ili više vrsta) koje su počele da rasvetljavaju našu evolutivnu prošlost i njen uticaj na zdravlje [5] . Cilj ovog rada jeste da ukaže na značaj evolucije u razumevanju i proučavanju psihičkih • br.…”
Section: Zašto Evolucioni Ugao Gledanja?unclassified
“…Relatively few researchers have looked into other populations [9,10]. This significant blind spot has greatly limited the search for biological clues to mental illness pathogenesis in a particular population group: as a result, associations that may be detected in one population group may not exist in others [9][10][11]. For example, it was demonstrated that severe SNPs associated with major depression are more common in Chinese people than in Caucasians (Sirtuin 1 gene (SIRT 1) rs12415800: 45% vs. 2%; phospholysine phosphohistidine inorganic pyrophosphate phosphatase gene (LHPP) rs35936514: 28% vs. 6%) [12].…”
Section: Introductionmentioning
confidence: 99%